Cohesive fracture model of rocks based on multi-scale model and Lennard-Jones potential. (1st April 2021) - Lin, Qindong; Li, Shihai; Feng, Chun; Wang, Xinquan
Highlights: The multi-scale model of rock is proposed based on the structural and fracture characteristics. The corresponding relation of deformation in the multi-scale model is established. The deformation energy is transformed into potential energy between molecules. The accuracy of the cohesive fracture model is verified through three numerical simulations. Abstract: With the aim of modelling the energy dissipation phenomenon during the initiation and propagation of cracks, a novel cohesive fracture model is proposed in this study based on the multi-scale model of rocks and the Lennard-Jones potential between non-bonding molecules. The proposed model establishes the corresponding relationship of deformation in the multi-scale model of rocks and suggests that the fracture energy is essentially the manifestation of the transformation of deformation energy into potential energy between molecules. First, the multi-scale model of rocks is established based on the structural characteristics and fracture characteristics of rocks, and the corresponding relation of deformation at different scales is analysed. Thereafter, the force and potential energy equations of the cohesive fracture model corresponding to the tensile and shear processes are established. Finally, the accuracy of the cohesive fracture model is verified through three numerical simulations. The results indicate that the cohesive fracture model can accurately fit the theoretical values and experimental results in the Mode-I and Mode-II tests. In the uniaxial compression test, the cohesive fracture model can accurately simulate the uniaxial compressive strength and fracture pattern of rocks.